Synthesis and Characterization of Phosphorus- and Carborane-Containing Polyoxanorbornene Block Copolymers - Kahraman, Gizem; Wang, De-Yi; von Irmer, Jonas; Gallei, Markus; Hey-Hawkins, Evamarie; Eren, Tarik (MDPI, 2019)
Grubbs-catalyzed ring-opening metathesis polymerization (ROMP) of carborane- and phosphonate-containing monomers has been used for the generation of hybrid block copolymers. Molecular weights with M-n of 50,000 g/mol were readily obtained with polydispersity index values, D, between 1.03-1.08. Reaction of the phospha ester and carborane substituted oxanorbornene block copolymer with trimethylsilyl bromide led to a new polymer with phosphonic acid functionalities. In application studies, the phospha-carborane functionalized block polymer was tested as heat resistance material. Thermal stability was investigated by thermal gravimetric analysis (TGA) and microscale combustion calorimetry (MCC) analysis. Thermal treatment and ceramic yield under air were directly correlated to the carborane content of the block copolymer. However, phosphorus content in the polymer was more crucial for the char residues when heated under nitrogen atmosphere. The peak heat release rate (PHRR) increased as the number of phosphonate functionalities increased. However, corresponding phosphonic acid derivatives featured a lower heat release rate and total heat release. Moreover, the phosphonic acid functionalities of the block copolymer offer efficient chelating capabilities for iron nanoparticles, which is of interest for applications in biomedicine in the future. The complexation with iron oxide nanoparticles was studied by transmission electron microscopy (TEM) and inductively coupled plasma mass spectrometry (ICP-MS).
Keywords: carboranes; phosphonate esters; block copolymers; ROMP; hybrid materials; OPENING METATHESIS POLYMERIZATION; IRON-OXIDE NANOPARTICLES; DIBLOCK COPOLYMERS; O-CARBORANE; POLYMERS; MONOMERS; MICELLES; ACIDS; Polymer Science